2015
DOI: 10.1074/jbc.m114.634923
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Triplex DNA Unwinding Activity of ChlR1 Helicase

Abstract: Background: DNA triplex helix structures are alternate DNA structures that can be a source of genomic instability. Results: ChlR1 helicase has a novel and distinct triplex DNA unwinding activity. Conclusion: ChlR1 defends genome integrity by resolving triplex DNA structures. Significance: The processing of triplex DNA substrates by proteins such as ChlR1 plays critical roles in genome maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 69 publications
1
50
0
Order By: Relevance
“…In vitro studies have demonstrated that different DNA helicases, such as RecQ [Bacolla et al., ], DHX9 [Jain et al., ], and ChlR1 [Guo et al., ], are able to resolve triplex DNA structures [León‐Ortiz et al., ], and that the lack of these activities is generally associated with genomic instability [Bacolla et al., ; Jain et al., ; Guo et al., ]. Thus, it is possible that DNA helicase activity might also contribute to the processing of R•Y‐rich mirror repeats following an initial single strand break.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have demonstrated that different DNA helicases, such as RecQ [Bacolla et al., ], DHX9 [Jain et al., ], and ChlR1 [Guo et al., ], are able to resolve triplex DNA structures [León‐Ortiz et al., ], and that the lack of these activities is generally associated with genomic instability [Bacolla et al., ; Jain et al., ; Guo et al., ]. Thus, it is possible that DNA helicase activity might also contribute to the processing of R•Y‐rich mirror repeats following an initial single strand break.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, Timeless interacts with DDX11 29,36,50 , and this interaction has been shown to be important for sister chromatid cohesion 50 and preservation of fork progression in perturbed conditions 36 . Further, in vitro, DDX11 can unwind several DNA structures including G4s [38][39][40] and the activity of DDX11 is stimulated by Timeless 36 . Recent work has shown that DDX11 interacts with Timeless through a domain in exon 4 50 .…”
Section: Ddx11 Ensures Processive G4 Replication In Vivomentioning
confidence: 99%
“…Triplex-unwinding helicases, on the other hand, are still largely unknown. Reports have demonstrated in vitro triplex-unwinding activity for several proteins, namely human Dhx9 (358), Ddx11 (359), and BLM and WRN helicases (360) as well as the yeast Stm1 protein (361). However, in vivo evidence for the involvement of these helicases in triplex unwinding is scarce.…”
Section: How To Maintain Hard-to-replicate Expandable Repeats?mentioning
confidence: 99%